Worldwide Genetic Diversity for Mineral Element Concentrations in Rice Grain. Issue 1 (1st January 2015) - Pinson, Shannon R. M; Tarpley, Lee; Yan, Wengui; Yeater, Kathleen; Lahner, Brett; Yakubova, Elena; Huang, Xin‐Yuan; Zhang, Min; Guerinot, Mary Lou; Salt, David E.
ABSTRACT: With the aim of identifying rice ( Oryza spp.) germplasm having enhanced grain nutritional value, the mineral nutrient and trace element concentrations (or ionome) of whole (unmilled) grains from a set of 1763 rice accessions of diverse geographic and genetic origin were evaluated. Seed for analysis of P, Mg, K, S, Ca, As, Cd, Co, Cu, Fe, Mn, Mo, Ni, Rb, Sr, and Zn concentrations by inductively coupled plasma mass spectrometry was produced over 2 yr in Beaumont, TX, under both flooded and unflooded watering regimes. The distributions of all element concentrations analyzed were skewed toward higher concentration. A significant portion of this ionomic variation has a genetic basis (broad sense heritabilities 0.14–0.75), indicating an ability to breed for improved grain concentration of all elements except possibly Ni. Variation in grain elemental concentrations was not strongly associated with plant height, heading time, or grain shape, suggesting these physiological factors are not of primary importance in controlling ionomic variation in rice grain. Accessions high in specific elements were sometimes found to have similar genetic or geographic origins, suggesting they share a heritable mechanism underlying their enhanced ionomes. For example, accessions with high Ca, Mg, or K were more common in the indica than in the japonica subgroup; low As was most common among temperate japonica accessions; and several lines high in Mo originated in Malaysia or adjacent Brunei.